A CFD analysis of flow around a disc - Lukes, R. A.; Hart, J. H.; Potts, J.; Haake, S. J. (Procedia Engineering, 2014)
Discus, disc golf and ultimate Frisbee are all sports that utilise rotating disc projectiles. The aim of this study was to use computational fluid dynamics (CFD) examine the flow over a disc and in doing so determine which CFD model is most suited to examining the aerodynamics of sports disc projectiles. All of the CFD analysis was carried out using ANSYS-Fluent V6.3. The study initially compared experimental and CFD data of flow around a simple non-rotating parametric disc, with a thickness to diameter ratio of 0.1. Aerodynamic coefficients and surface flow visualisations were compared. Three models within ANSYS-Fluent gave steady converged solutions; standard k-å, realizable k-å and standard k-ù. The standard k-ù model gave unrealistic aerodynamic coefficients and was discounted. The two k-å models were used for the second stage of the study, simulating the flow around a disc golf disc, called a Floater. The geometry of the disc was captured using a 3D non-contact laser scanner. Aerodynamic coefficients and surface flow visualisations showed good agreement between the two k-å models. The standard k-å model was deemed the most suitable for a study of flow around a sports disc, mostly due to its more accurate simulations of the parametric disc. The results were used to further examine the flow, looking at separated flow on the discs surface with increasing angle of attack and the structure of the wake. The study identified which CFD model is most suited to the simulation of flow over a sports disc and in doing so provided a platform for using CFD for future disc aerodynamics studies.